The Study of Magnetic Force in Electromagnetic Forming of Small Size Sheet. Issue 8 (20th April 2015) - Chen, Xiaowei; Wang, Wenping; Wan, Min; Long, Anlin; Whan Yoon, Jeong; Hodgson, Peter; Beynon, John
<x xml:space="preserve">Abstract</x> It is essential to calculate magnetic force in the process of studying electromagnetic sheet forming. Calculating magnetic force is the basis of analyzing sheet deformation and optimizing technical parameters. In order to calculate magnetic force in electromagnetic forming of small size sheet, finite element software ANSYS/EMAG was used. Small size sheet means that sheet length or sheet width, or both, is/are shorter than plane dimensions of coil. Based on numerical simulation and experiment, induced current crowding effect was studied, and the influence of charging voltage, capacitance, separation distance, and relative position between coil and sheet on magnetic force were analyzed. The results show that, in the process of electromagnetic forming of small size sheet, induced current crowding effect will be caused by the variation of induced current channel width on the sheet, which seriously influence the magnetic force distribution, and the non‐uniformity degree of magnetic force distribution is increased nearly linearly with the variation of induced current channel width; the desirable magnetic force distribution can be achieved by adjusting the relative position between coil and sheet. And, magnetic force is increased with the increase of capacitance and charging voltage. At the same time, the variation period of magnetic force increased with the increasing of capacitance. Magnetic force decreased obviously with the increasing of separation distance between coil and sheet. At last, the experiment of sheet impact balls pad mold under magnetic force and electromagnetic V‐shape forming was performed to confirm the validity of numerical simulation result.